An appraisal of the legality of the referendum: A study of Iraqi Kurdistan Region - Qader, Sanh Sharif; Mohd Anuar, Haslinda; Ahmad, Rusniah (JARDCS, 2019)
Referendum is usually an option for deciding an issue mostly political. It is a legal means of achieving set objectives among people. Places like the East Timor and south Sudan have employed to gain statehood. This is possible as it have been proved legally worthy of the peoples. The article aims at discussing the legality of referendum in the achievement of people’s aspiration towards state formation. Secondary source materials will provide major source of data. The paper will add to the pool literature on legality of referendum. It will shed more on the legality of referendum conducted by the Iraqi of Kurdistan region